Pine seed protein electrophoretic profiles as taxonomic characters (2002)
Seed proteins play a very important role in germination. Seeds from a single taxon have a highly stable composition of storage protein. This stability is useful in agronomic, ecological, physiological, taxonomic, molecular and phyto-pathological studies. This paper describes the electrophoretic characterisation in acrylamide gels of seed protein from five pine species (Pinus cembroides, P ayacahuite, P durangensis, P engelmanii, P cooperi and P maximartinezii) from México to determine the importance of their protein profile as biochemical markers in taxonomy. The results suggest that pine reserve protein electrophoretic profiles have chemical attributes having taxonomic importance at subgenus and species level.